Complement-independent binding of microorganisms to primate erythrocytes in vitro by cross-linked monoclonal antibodies via complement receptor 1. - Powers, J H (1995)
Under certain circumstances, soluble antigens, particulate antigens, and/or microorganisms have been shown to bind to primate erythrocytes via complement receptor 1 (CR1) in the presence of specific antibodies and complement. This immune adherence reaction, specific for CR1, can lead to neutralization of antigens in the circulation and their subsequent clearance from the blood. The present experiments utilized cross-linked monoclonal antibody complexes (heteropolymers) with specificity for both CR1 and either 35S-labeled herpes simplex virus capsid or Haemophilus influenzae as prototype viral and bacterial particulate antigens, respectively. In each case, the respective specific heteropolymers facilitated binding of the target antigens (> or = 70 to 90%) in vitro to erythrocytes in the absence of complement. Several experimental protocols were employed to demonstrate that heteropolymers mediate specific, rapid (> or = 30 s), and quantitative binding of prototypical particulate pathogens to human and monkey erythrocytes but not to sheep erythrocytes, which lack CR1. These results extend the potential use of the erythrocyte-heteropolymer system to the neutralization and clearance of particulate viral and bacterial pathogens from the blood.